Improving vasomotor symptoms; psychological symptoms; and health-related quality of life in peri- or post-menopausal women through yoga: An umbrella systematic review and meta-analysis. (October 2017) - Shepherd-Banigan, M.; Goldstein, K.M.; Coeytaux, R.R.; McDuffie, J.R.; Goode, A.P.; Kosinski, A.S.; Van Noord, M.G.; Befus, D.; Adam, S.; Masilamani, V.; Nagi, A.; Williams, J.W.
Highlights: This systematic review examined the effectiveness of yoga on vasomotor symptoms, psychological symptoms, health-related quality of life, and adverse effects in peri- or post-menopausal women. We used a novel systematic review methodology which used data from existing systematic reviews and data from randomized controlled trials. Contrary to results from past systematic reviews, we find that yoga may contribute to improvements in vasomotor symptoms and psychological symptoms in peri- or post-menopausal women. Abstract: Objectives: Vasomotor symptoms (VMS), commonly reported during menopausal transition, negatively affect psychological health and health-related quality of life (HRQoL). While hormone therapy is an effective treatment, its use is limited by concerns about possible harms. Thus, many women with VMS seek nonhormonal, nonpharmacologic treatment options. However, evidence to guide clinical recommendations is inconclusive. This study reviewed the effectiveness of yoga, tai chi and qigong on vasomotor, psychological symptoms, and HRQoL in peri- or post-menopausal women. Design: MEDLINE, Cochrane Database of Systematic Reviews, EMBASE, CINAHL and the Allied and Complementary Medicine Database were searched. Researchers identified systematic reviews (SR) or RCTs that evaluated yoga, tai chi, or qigong for vasomotor, psychological symptoms, and health-related quality of life (HRQoL) in peri- or post-menopausal women. Data were abstracted on study design, participants, interventions and outcomes. Risk of bias (ROB) was assessed and updated meta-analyses were performed. Results: We identified one high-quality SR (5 RCTs, 582 participants) and 3 new RCTs (345 participants) published after the SR evaluating yoga for vasomotor, psychological symptoms, and HRQoL; no studies evaluated tai chi or qigong. Updated meta-analyses indicate that, compared to controls, yoga reduced VMS (5 trials, standardized mean difference (SMD) −0.27, 95% CI −0.49 to −0.05) and psychological symptoms (6 trials, SDM −0.32; 95% CI −0.47 to −0.17). Effects on quality of life were reported infrequently. Key limitations are that adverse effects were rarely reported and outcome measures lacked standardization. Conclusions: Results from this meta-analysis suggest that yoga may be a useful therapy to manage bothersome vasomotor and psychological symptoms.